Risperidone Inhibits Contractions Induced by Serotonin and Histamine and Reduces Kþ Currents in Smooth Muscle of Human Umbilical Artery - Iveli, María Florencia (2010)
Risperidone is an antipsychotic commonly used during pregnancy. Because it can cross the placental barrier, our objective was to evaluate its actions on the smooth muscle of the human umbilical artery (HUA). Risperidone preincubation (1-300 nmol/L for 20 minutes) produced a significant decrease in maximum force development induced by serotonin or histamine inHUArings. When applied on top of stable contractions induced by these agonists risperidone produced quick relaxations (IC50 ¼ 1 nmol/L for serotonin and 72 nmol/L for histamine). Risperidone induced the contraction of vascular rings depolarized by 40 mmol/L extracellular Kþ but not in the case of 80 mmol/LKþ, suggesting inhibition of Kþ channels. The patch-clamp technique showed that risperidone (3 nmol/L) inhibited whole-cell Kþ currents in freshly isolated HUA smooth muscle cells. Our results are the first showing risperidone effects in human vascular smooth muscle and highlight that its use during pregnancy should be adequately monitored.